The Scholarship of Teaching and Learning in Higher Education: An Evidence-Based Perspective
XVI, 814 p.
Keywords: Pivotal to the transformation of higher education in the 21st Century is the nature of pedagogy and its role in advancing the aims of various stakeholders. This book brings together pre-eminent scholars from Australia, Canada, Europe, the Middle East, and the USA to critically assess teaching and learning issues that cut across most disciplines. In addressing long-standing and newly emerging issues, the researchers examine the scientific evidence on what constitutes effective teaching in college classrooms, on the psychometric integrity of measures of teaching effectiveness, and on the use of such measures for tenure, promotion, and salary decisions. Systematically explored throughout the book is the avowed linkage between classroom teaching and motivation, learning, and performance outcomes in students. In so doing, the book deals with the nexus between knowledge production by researchers and knowledge utility for end-users made up of classroom instructors, department heads, deans, directors, and policymakers. The book will appeal to researchers interested in teaching and learning, faculty members developing evidence-based pedagogical practices, academic administrators and policymakers responsible for instituting teaching and learning protocols, and faculty development officers promoting the effective teaching practices.